PRODUCTIVITY IN REPARATION ACTIVITIES IN SHIPYARD OF PALABUHANRATU FISHING PORT OF WEST JAVA PROVINCE - Juita Rodiarni Sitorus; Syaifuddin Syaifuddin; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted to measure the level of productivity in ship repair activities and determine the factors that influence the increase in productivity in ship repair activities. This research was carried out in April until May 2018 at the shipyard of the Palabuhanratu Fishing Port, Sukabumi Regency, West Java Province. The method used is a survey method by knowing directly the productivity of reparations in shipyards. Reparation is an overall activity about repairing a ship, starting from the collision on the part of the ship that is leaking, painting, replacing weathered wood, cleaning the hull skin and repairing the damaged engine. Productivity is a comparison between spending and input. The factors that most influence the shipyard productivity from the measured performance indicators are the number of employee absenteeism or labor where the importance of the weight is 30%, the ship repair workforce and effective working hours which have a weighting of 20% each. Based on the results of the measurement of performance indicators for 5 years with the Objective Matrix method, the productivity index of performance indicators from 2013 to 2017 has experienced a considerable decline due to the decreasing number of vessels carrying out ship repairs. Keywords: Ship Repair, Productivity, Measurement of Performance Indicators